2021
DOI: 10.1007/s11481-020-09979-8
|View full text |Cite
|
Sign up to set email alerts
|

ACE-2-interacting Domain of SARS-CoV-2 (AIDS) Peptide Suppresses Inflammation to Reduce Fever and Protect Lungs and Heart in Mice: Implications for COVID-19 Therapy

Abstract: COVID-19 is an infectious respiratory illness caused by the virus strain severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and until now, there is no effective therapy against COVID-19. Since SARS-CoV-2 binds to angiotensin-converting enzyme 2 (ACE2) for entering into host cells, to target COVID-19 from therapeutic angle, we engineered a hexapeptide corresponding to the ACE2-interacting domain of SARS-CoV-2 (AIDS) that inhibits the association between receptor-binding domain-containing spike S1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 33 publications
1
49
1
Order By: Relevance
“…Several organ-protecting effects of this hexapeptide justify more intense work in this aspect [19]. However, in the current study we demonstrated that in-silico specific amino acid alteration in the highly conserved S protein of the SARS CoV 2 can potentially block its ACE2 Where, SM3 and DM2 showed more affinity to ACE2.…”
Section: Mutation Induction and Competitive Inhibition Of Spike Glycocontrasting
confidence: 46%
See 1 more Smart Citation
“…Several organ-protecting effects of this hexapeptide justify more intense work in this aspect [19]. However, in the current study we demonstrated that in-silico specific amino acid alteration in the highly conserved S protein of the SARS CoV 2 can potentially block its ACE2 Where, SM3 and DM2 showed more affinity to ACE2.…”
Section: Mutation Induction and Competitive Inhibition Of Spike Glycocontrasting
confidence: 46%
“…Similar type of study suggests that engineered ACE2 receptor traps can neutralize SARS-CoV-2 [18]. A hexapeptide in core of spike RBD inhibits the association between spike S1 and ACE-2 [19].…”
Section: Mutation Induction and Competitive Inhibition Of Spike Glycomentioning
confidence: 77%
“…In a previous study, the effectiveness of peptides against the S1 protein of SARS-CoV-1 was established [ 28 ]. In another study, a corresponding hexapeptide to the ACE-interacting domain of SARS-CoV-2 (AIDS) has been found to disrupt the association between RBD-ACE2 in mice[ 29 ]. Karoyan and colleagues designed peptide-mimics which has been found to inhibit S protein with inhibitory concentration (IC50) in nanomolar range [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…But as this peptide is a very short fragment having no higher-order of protein structure so the effect may not be due to the complementarily based S1 and ACE-2 binding. Several organ-protecting effects of this hexapeptide justify more intense work in this aspect [19]. However, in the current study we demonstrated that in-silico specific amino acid alteration in the highly conserved S protein of the SARS CoV 2 can potentially block its ACE2 binding, hence minimize the viral infection.…”
Section: Resultsmentioning
confidence: 58%
“…Several organ-protecting effects of this hexapeptide justify more intense work in this aspect [19]. However, in the current study we demonstrated that in-silico specific amino acid alteration in the highly conserved S protein of the SARS CoV 2 can potentially block its ACE2 Whereas for complete spike glycoprotein (6vyb1), Mutated CUT4 get more preference in ACE2 attachment as they showed binding affinity of -11.8, -11.9 and -11.9 respectively.…”
Section: Mutation Induction and Competitive Inhibition Of Spike Glycoprotein -Ace2 Attachmentmentioning
confidence: 56%